Apple (Malus × domestica Borkh.) dormancy – a review of regulatory mechanisms and agroclimatic requirements - González Noguer, Carlota; Delgado, Alvaro; Else, Mark; Hadley, Paul (Frontiers in Horticulture, 2023)
Dormancy enables apple trees (Malus × domestica Borkh) to survive unfavourable weather conditions. The accumulation of cold temperatures during winter is required to release dormancy, whilst heat accumulation in spring promotes bud break and blooming. Chilling and heat requirements are used to anticipate cultivars' suitability to local agroclimatic conditions. This review summarises recent advances on the physiological and genetic mechanisms regulating dormancy in apple trees; and presents a compilation of available chilling and heat requirements for apple cultivars. Information shows a wide range of chilling requirements in existing cultivars. However, results reported for the same cultivar are highly variable between locations and methods used to estimate chilling; raising concerns on the suitability of using chill requirements to inform planting decisions. In the context of climate change, it is essential to ensure current knowledge on the physiological and genetic mechanisms regulating bud break guides the development of improved models that can generate better estimates of chilling and heat requirements in apple.